2017
DOI: 10.26525/jtfs2017.29.3.380388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression and Quality Of

et al.

Abstract: Agarwood, precious resinous trunks or branches derived from Aquilaria plants, is widely used in incense and perfume. However, due to its low yield and high production cost, a novel stimulating method is required to produce agarwood rapidly and effectively. We studied the biologically agarwood-inducing technique (Agar-Bit) that achieved high yield and qualified production. In this study the gene expressions and chemical compositions in agarwood obtained from Aquilaria sinensis trees using Agar-Bit were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Naturally, agarwood formation is often linked to the physical wounding or damage of Aquilaria trees caused by thunder strike, animal grazing, pest and disease infestations (Rasool and Mohamed, 2016; Wu et al, 2017). These events expose the inner part of the trees toward pathogenic microbes, which elicit the defense mechanism of Aquilaria to initiate the resin production.…”
Section: Agarwood Induction Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Naturally, agarwood formation is often linked to the physical wounding or damage of Aquilaria trees caused by thunder strike, animal grazing, pest and disease infestations (Rasool and Mohamed, 2016; Wu et al, 2017). These events expose the inner part of the trees toward pathogenic microbes, which elicit the defense mechanism of Aquilaria to initiate the resin production.…”
Section: Agarwood Induction Approachesmentioning
confidence: 99%
“…Instead of relying on external stimuli to trigger plant responses, either by mechanical wounding or biological inoculum, some induction approaches have been developed to introduce signaling molecules directly and specifically into Aquilaria trees to initiate agarwood resin biosynthesis pathways (Liu Y. et al, 2013; Wu et al, 2017). Chemical inducers normally comprise of phytohormones, salts, minerals and biological-derived substances (Zhang et al, 2012; Liu Y. et al, 2013; Van Thanh et al, 2015).…”
Section: Agarwood Induction Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another new technique for agarwood induction is known as biologically agarwood-inducing technique (Agar-Bit), which yields better quality and quantity of agarwood. It was found that the Agar-Bit method upregulated the expression of some biological synthase genes (farnesyldiphosphate synthase, sesquiterpene synthase, and chalcone synthase) compared to the mechanically stimulated agarwood (Wu et al, 2017; Tan et al, 2019). Subsequently, Subasinghe et al (2018) carried out an artificial induction by Aspergillus niger and F. solani for agarwood resin formation in Gyrinops walla trees.…”
Section: Agarwood Formation—mechanisms and Interventionsmentioning
confidence: 99%